2018
DOI: 10.3390/polym10010099
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Responsive Polymer Microgel-Gold Nanorods Composite Particles: Physicochemical Characterization and Cytocompatibility

Abstract: Abstract:In this paper, we report an easy route for preparing new metal nanorod-polymer composites consisting of gold nanorods, Au NRs, and temperature responsive copolymer "microgel" particles. The microgel particles of~200 nm in size, which contain carboxylic acid groups, were prepared by surfactant-free emulsion polymerization of a selected mixture made of N-isopropylacylamide and acrylic acid in the presence of a cross-linker N,N -methylenebisacrylamide. The electrostatic interactions between the cationic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…The homogeneous distribution of O, Te, and Sn in the SnTe NBs as well as the Au dots on the surface of the SnTe NBs can be further verified (Figure G,H,I,K,L). Simultaneously, the BSE-SEM further confirmed that Au NPs (white-colored spots) were evenly distributed and attached to the surface of the SnTe NBs under the BSE mode (Figure J), showing the distribution of Au NPs on SnTe NBs at a microscopic level . The white bright Au NPs surrounding the grayish-white dots (red arrow) in the BSE images proved that the as-prepared SnTe NBs were coated with a thin layer of Au, , which coincided with the observation in Figure E.…”
Section: Resultssupporting
confidence: 78%
“…The homogeneous distribution of O, Te, and Sn in the SnTe NBs as well as the Au dots on the surface of the SnTe NBs can be further verified (Figure G,H,I,K,L). Simultaneously, the BSE-SEM further confirmed that Au NPs (white-colored spots) were evenly distributed and attached to the surface of the SnTe NBs under the BSE mode (Figure J), showing the distribution of Au NPs on SnTe NBs at a microscopic level . The white bright Au NPs surrounding the grayish-white dots (red arrow) in the BSE images proved that the as-prepared SnTe NBs were coated with a thin layer of Au, , which coincided with the observation in Figure E.…”
Section: Resultssupporting
confidence: 78%
“…Khan et al developed gold nanorod-nanogel (Au NRs-nanogels) composite particles by connecting gold nanorods to poly(N-isopropyl acrylamide)-based nanogels via electrostatic interactions. [197] The Au NRs-nanogels showed reduced cytotoxicity to MCF-7 cells, human breast cancer cell line based on the results obtained in MTT and LDH assays. In addition, the nanogel almost eliminated the hemolytic activity of the gold nanorods on blood agar.…”
Section: Nanogelsmentioning
confidence: 99%
“…Conjugation of nanogels to biomaterials are often applied in order to modulate their biocompatibility. Khan et al [ 133 ] developed gold nanorod-nanogel (Au NRs-nanogels) composite particles by connecting gold nanorods to pNIPAM based nanogels via electrostatic interactions. The Au NRs-nanogels showed reduced cytotoxicity to MCF-7 cells based on MTT and LDH.…”
Section: Synthesis Properties and Biocompatibility Of Nanogelsmentioning
confidence: 99%
“…The Au NRs-nanogels showed reduced cytotoxicity to MCF-7 cells based on MTT and LDH. In addition, the nanogel almost eliminated the hemolytic activity of the gold nanorods on blood agar [ 133 ]. Ketoprofen, an anti-inflammatory drug, inhibits cyclooxygenase and shows high gastrointestinal toxicity.…”
Section: Synthesis Properties and Biocompatibility Of Nanogelsmentioning
confidence: 99%